Regulatory focus and preference reversal between hedonic and utilitarian consumption - Roy, Rajat; Ng, S. (John Wiley & Sons Ltd., 2012)
This article explores the impact of consumers’ regulatory goals on their relative focus on hedonic (versus utilitarian) benefits of products. Drawing from extant literature, we argue that promotion-focused consumers will exhibit more favorable attitude towards a product when its hedonic benefits are highlighted in comparison to its utilitarian benefits. Prevention-focused consumers on the other hand will exhibit more favorable attitude towards a product when its utilitarian benefits are highlighted in comparison to its hedonic benefits. We further argue that this effect is moderated by contextual factors, such as evaluation mode. In addition, we argue that the posited difference only holds when the hedonic and utilitarian products are evaluated individually.When the two products are evaluated jointly, both promotion and prevention-focused individuals will exhibit more favorable attitude towards the hedonic product. Two studies were conducted to test the hypotheses and findings supported our predictions.